136 Care of patients with progressive supranuclear palsy in the hospice setting: an audit. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hoddell, Kate; Dewhirst, Laura; Willis, Derek
Abstract : Hospices are increasingly focused on improving services for patients with life-limiting non-malignant conditions. Progressive supranuclear palsy (PSP) is a life-limiting progressive neurological disease which can be mistaken for Parkinson's disease early in its course. Symptoms progress rapidly within 5–7 years. Patients with PSP may have a high number of symptoms and will have a poor prognosis. This retrospective audit aimed to evaluate care provided to patients with PSP referred to Severn Hospice using the guide 'Pathway of Care for PSP: A guide for Health and Social Care Professionals' as the standard. It included all patients under hospice care since 2015. 20 patients were included, 8 of whom continued under hospice care. 7 patients had died and 5 discharged. Time between diagnosis and referral to our service was usually in the first year. Most patients were referred for 'medical assessment and support' and had more than 3 symptoms at referral. 5 patients were admitted to the hospice, 3 of whom died during admission. These patients had at least 4 symptoms at referral. 7 patients had no advance care planning (ACP) completed (defined as a do not resuscitate order (DNAR), preferred place of care (PPC), preferred place of death (PPD) and/or an advance decision to refuse treatment (ADRT)). Of the other patients 13 had a DNAR, 5 had a documented PPC, 5 had a documented PPD and 2 patients had an ADRT. Of the 7 who died, only 2 had a PPD; both achieved their PPD. This audit showed that while this is a small number of patients, this is a group with a high symptom burden at referral to palliative services. This suggests that palliative medicine has a role early in the patient journey. ACP was not fully completed in any audited patients indicating that this is an area requiring improvement.